Penerapan Teknik Pengaplikasian Bulu Ostrich Pada Busana Pesta - Nurtina, Nurtina; Mayasari, Peppy (PT. Riset Press International, 2025)
This study aims (1) to determine the process of applying the ostrich feather application technique to party dresses (2) to determine the results of applying the ostrich feather application technique to party dresses. In this study the method used is the creation of works consisting of four stages: pre-design, design, embodiment and presentation. The results of this study are the process of applying the ostrich feather application technique to party dresses. Starting from making designs according to the source of ideas obtained directly based on research and observations on the spot. The process of applying the ostrich feather application technique begins with placing ostrich feathers on the slits of the skirt and bra cups, then basting and sewing according to the design. The final result of applying the ostrich feather application technique to party dresses is in accordance with the source of ideas. The placement of ostrich feathers and the selection of material characteristics using plain white tulle with the addition of tulle sequins on the skirt so that it has a glamorous impression according to the source of ideas.